Dietary treatment of Crohn's disease: perceptions of families with children treated by exclusive enteral nutrition, a questionnaire survey. Issue 1 (December 2017) - Svolos, Vaios; Gerasimidis, Konstantinos; Buchanan, Elaine; Curtis, Lee; Garrick, Vikki; Hay, Jacqueline; Laird, Susan; Munro, Joanna; Gaya, Daniel; Russell, Richard; Hansen, Richard
Abstract Background Diet is strongly associated with the aetiology of Crohn's Disease (CD) and exclusive enteral nutrition (EEN) is the primary induction treatment in paediatric CD. This study explored opinions around the use of EEN and alternative novel, solid food-based diets (SFDs) expressed by paediatric patients with CD, previously treated with EEN and their parents. Methods This anonymous questionnaire surveyed families of CD patients treated with EEN over 1 year. Two questionnaire forms were completed; one asking the patients' opinions and another referring to their main carer. This questionnaire explored participants' demographic characteristics; acceptability of a repeat EEN course to treat a future flare (EEN repeat); their opinion on how difficult EEN would be compared to an example SFD; and their intention to participate in a future clinical trial assessing the therapeutic efficacy of an SFD in CD. Results Forty-one families of CD patients were approached with 29 sending replies (71%). Most of our participants were positive on completing another EEN course, however the majority would choose an SFD alternative (Patients:66, Parents:72%). Both patients and their parents rated EEN to be more difficult to adhere to compared to an example SFD (p < 0.05), and their ratings were strongly correlated (EEN:r = 0.83, SFD:r = 0.75, p < 0.001). The majority of our respondents would agree to participate in a clinical trial assessing an SFD's effectiveness (Patients:79, Parents:72%) for the management of active CD. Conclusions While patients with CD and their families would accept an EEN repeat, the majority would prefer an SFD alternative. CD families surveyed are supportive of the development of solid food-based dietary treatments.